Estimating temperature exposure of burnt bone — A methodological review. Issue 3 (May 2015) - Ellingham, Sarah T.D.; Thompson, Tim J.U.; Islam, Meez; Taylor, Gillian
Abstract: Forensic anthropologists are frequently confronted with the need to interpret burnt bone. Regardless of the context, one of the key factors for the correct interpretation of the remains and a reconstruction of the incidents leading to incineration is the estimation of the maximum exposure temperature. The recent years have seen an influx in experimental research focusing on temperature estimation, spanning from colour assessment, mechanical strength measurements, histology and structural observations, biochemical changes and crystallinity studies, vastly advancing the understanding of heat induced changes in bone, thus facilitating a more accurate interpretation. This paper draws together and evaluates all currently available methodologies for temperature estimation. Highlights: Currently available methods for temperature estimation from burnt bone are reviewed and compared Advantages and drawbacks of each methodology of burn temperature estimation are discussed Areas of research in which further studies are required are evinced The most accurate result to estimate temperature from burnt bone is achieved by combining quantitative and qualitative data